A Path From Sustainable Nutrition to Nutritional Sustainability of Complex Food Systems - Smetana, Sergiy M.; Bornkessel, Sabine; Heinz, Volker (Frontiers in Nutrition, 2019)
Integration of nutritional and sustainable aspects is a complex task tackled by a few scientific concepts. They include multiple dimensions and functions of food systems trying to provide solutions for harmonic co-evolution of humanity and planet Earth. “Nutritional Sustainability” is differentiated from other concepts which combine nutrition and sustainability as it not only sets environmental sustaining capacity as a baseline level for balanced nutrition, but also aims for the search of food system driving nodes. It does not aim for the support of solutions of producing enough or more food for increasing population (sustainable nutrition), neither does it contradict other similar concepts (sustainable nutrition security, nutritional life cycle assessment). However, it calls for more definite estimation of the carrying capacity of the environment on personal, local and national levels for the development of more efficient solutions of nutrition balanced in the limits of environmental carrying capacity. The review is providing a few examples of advances in nutritional science (personalized nutrition, nutrigenetics), food technology (personalized food processing, food ecodesign) and food complex systems (artificial intelligence and gut microbiome), which have a great potential to progress sustainable food systems with Nutritional Sustainability set as a guiding concept.